Association of abdominal obesity to hypertension history in Panamanian college students - Luis Gabriel Rangel Caballero; Lourdes Luz Irribaren Llorente; Natalie Patricia Vásquez Mendoza; Isabel Anayansi Ardines Bailey; Alba Liliana Murillo López (Archivos Latinoamericanos de Nutrición)
Introduction: Abdominal obesity is the excess of deposits of fat in the abdominal region and it is an independent risk factor for cardiovascular disease. Hypertension is a metabolic risk factor for non-communicable diseases, and it is the leading cause of premature death in the world. Objective: to determine the association between abdominal obesity and hypertension, hyperglycemia, and hyperlipidemia history in Panamanian college students. Materials and methods: Analytical cross- sectional study carried out in 434 college students from four different cities of a private university in Panamá. Every participant in the study signed written consent. Abdominal obesity was established as a waist circumference of ≥80 cm in women and ≥90 cm in men. Hypertension, hyperglycemia, and hyperlipidemia history were established with the basic questionnaire in the STEPS World Health Organization Instrument. Descriptive, as well as bivariate and multivariate analysis, were realized using logistic regression models. Results: 36.41% of participants had abdominal obesity (no statistically significant difference was found by sex). 14.29%, 9.22%, and 13.82% of the students surveyed reported a history of hypertension, hyperglycemia, and hyperlipidemia respectively (no statistically significant difference was found by sex). After adjusting by sex, age, and socioeconomic level, abdominal obesity was associated with hypertension antecedent (OR=2.06, CI 95%: 1.183-3.597, p=0.011). Conclusions: Students who evidenced abdominal obesity were more likely to have a hypertension history. The study recommends implementing strategies that promote healthy living habits to reduce future cardiovascular risk in the Panamanian university population